2017
DOI: 10.1002/btpr.2462
|View full text |Cite
|
Sign up to set email alerts
|

Low glucose concentrations within typical industrial operating conditions have minimal effect on the transcriptome of recombinant CHO cells

Abstract: Typically, mammalian cell culture medium contains high glucose concentrations that are analogous to diabetic levels in humans, suggesting that mammalian cells are cultivated in excessive glucose. Using RNA-Seq, this study characterized the Chinese hamster ovary (CHO) cell transcriptome under two glucose concentrations to assess the genetic effects associated with metabolic pathways, in addition to other global responses. The initial extracellular glucose concentrations used represented high (30 mM) and low (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 99 publications
(227 reference statements)
0
9
0
Order By: Relevance
“…Numerous CHO transcriptomics studies have been performed over the past decade comparing changes in culture conditions including hyperosmolarity, temperature shift, glucose concentration, lactate concentration, and sodium butyrate treatment . Differences in growth phases, growth rates, productivity, and protein glycosylation have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous CHO transcriptomics studies have been performed over the past decade comparing changes in culture conditions including hyperosmolarity, temperature shift, glucose concentration, lactate concentration, and sodium butyrate treatment . Differences in growth phases, growth rates, productivity, and protein glycosylation have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies aiming to enhance recombinant protein production focus on maximizing specific protein productivity while maintaining high viable cell density in culture for long periods. In this context, the operational conditions (e.g., temperature or medium composition) play a significant role in culture performance and proper handling of the cultures may indeed enable considerable increases in r-protein production [ 5 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, most industrially relevant culture media for mammalian cells contain a glucose concentration from 25 to 35 mM [ 29 , 32 ]. Therefore, 30 mM is the average glucose concentration for standard mammalian cell culture media, and concentrations below 20 mM are considered low [ 12 , 28 ], while concentrations above 40 mM are considered high [ 11 , 32 ], as compared with typical culture media. In cultures under very glucose-limited conditions (below 2 mM), cells have a drastically reduced intracellular concentration of ATP, amino acids and TCA cycle metabolites [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gowtham et al also reported their transcriptome analysis of recombinant CHO cells grown under two glucose concentrations to assess the genetic effects associated with metabolic pathways and global responses. They indicated that the transcriptome data support the continued development of low glucose‐based processes to control lactate . Another transcriptome analysis using both microarray and RNA‐Seq was reported by Yuk et al to explore the MOA of high copper concentrations’ impact on lactate metabolism .…”
Section: Introductionmentioning
confidence: 91%
“…The advent of Next Generation Sequencing (NGS) technologies and the availability of CHO reference genomes have enabled the systematic analysis of CHO biology and its capacity for recombinant protein production . Transcriptome analyses by microarray and RNA‐Seq have become commonly applied to unveil physiological insights into global gene expression related to cell culture performance . As an example, Shridhar et al recently reported using a high‐performance microarray platform to examine the transcriptome of CHO cells grown in the presence and absence of serum.…”
Section: Introductionmentioning
confidence: 99%